1995
DOI: 10.1128/mcb.15.4.1923
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Binding Specificity of the PAR Basic Leucine Zipper Protein VBP Partially Overlaps Those of the C/EBP and CREB/ATF Families and Is Influenced by Domains That Flank the Core Basic Region

Abstract: The PAR subfamily of basic leucine zipper (bZIP) factors comprises three proteins (VBP/TEF, DBP, and HLF) that have conserved basic regions flanked by proline-and acidic-amino-acid-rich (PAR) domains and functionally compatible leucine zipper dimerization domains. We show that VBP preferentially binds to sequences that consist of abutted GTAAY half-sites (which we refer to as PAR sites) as well as to sequences that contain either a C/EBP half-site (GCAAT) or a CREB/ATF half-site (GTCAT) in place of one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 33 publications
3
50
0
3
Order By: Relevance
“…Alternatively, the C/EBPs might promote neurogenesis by sequestering activating transcription factor 5 (ATF5), another transcription factor of the leucine zipper family that maintains neural precursors in an undifferentiated state (Angelastro et al, 2003(Angelastro et al, , 2005. Previous work has shown that C/EBPs and ATFs can heterodimerize (Shuman et al, 1997) and that the heterodimers bind to different DNA binding sites than do either ATF or C/EBP homodimers (Haas et al, 1995). Thus, the relative levels and activation state of ATF5 versus C/EBPs may well determine whether or when a precursor differentiates into a neuron.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the C/EBPs might promote neurogenesis by sequestering activating transcription factor 5 (ATF5), another transcription factor of the leucine zipper family that maintains neural precursors in an undifferentiated state (Angelastro et al, 2003(Angelastro et al, , 2005. Previous work has shown that C/EBPs and ATFs can heterodimerize (Shuman et al, 1997) and that the heterodimers bind to different DNA binding sites than do either ATF or C/EBP homodimers (Haas et al, 1995). Thus, the relative levels and activation state of ATF5 versus C/EBPs may well determine whether or when a precursor differentiates into a neuron.…”
Section: Discussionmentioning
confidence: 99%
“…1; the basic amino acid region and the leucine zipper region are indicated. The basic amino acid region of NF-IL3A appears to be more related to members of the proline-and acidic amino acid-rich (PAR) family of bZIP transcription factors, such as albumin promoter D-box-binding protein (DBP), thyrotroph embryonic factor (TEF), and hepatic leukemia factor (HLF), than to members of the AP-1 family (11,15,16,26).…”
Section: Resultsmentioning
confidence: 99%
“…Although their sequence similarity is distant, they share a consensus DNA-binding site (Cowell et al, 1992;Drolet et al, 1991;Falvey et al, 1995;Fonjallaz et al, 1996;Haas et al, 1995;Hunger et al, 1992). One of these, E4BP4 (also known as NFIL3), can act in different contexts as a transcriptional repressor or activator (Cowell et al, 1992;Lai and Ting, 1999;Zhang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%